The determinants of foreign direct investment in Malaysia: A case for electrical and electronic industry - Tang, Chor Foon; Yip, Chee Yin; Ozturk, Ilhan (Elsevier B.V, 2014)
This study attempts to analyse the determinants of inward FDI in the electrical and electronic (E&E) industry in Malaysia using bounds test approach for the 1980–2008 period. It is found that GDP, real exchange rate, financial development, corporate income tax, macroeconomic uncertainty and social uncertainty factors significantly affect inward FDI in E&E sector in Malaysia. Empirical results indicate that GDP, real exchange rate, financial development and macroeconomic uncertainty are positively related to inward FDI in E&E sector in the long run. However, corporate income tax and social uncertainty have a negative impact on inward FDI in E&E sector. Furthermore, the Granger causality results also indicate that all explanatory variables Granger-cause FDI in the long-run, but in the short-run only macroeconomic and social uncertainties Granger-cause FDI. The impact of social uncertainty is found to be greater than macroeconomic uncertainty. Thus, foreign investors in E&E sector seem to be more concern about the level of social security and safety when choosing their investment destination.